Durable and deep response to CVD chemotherapy in SDHB-mutated metastatic paraganglioma: case report - Zhang, Chenyan; Wei, Yuanfeng; Cheng, Ke; Cao, Dan (Frontiers in Endocrinology, 2024)
IntroductionSuccinate dehydrogenase subunit B (SDHB)-mutated paragangliomas (PGLs) are rare neuroendocrine tumors characterized by increased malignancy, readily metastasizing, and poorer prognosis. Here we report a case of SDHB-mutated metastatic PGL, wherein the patient showed significant tumor shrinkage and complete symptom remission following chemotherapy. We aim to contribute additional evidence to the existing knowledge associated with SDHB-mutated PGLs.Case reportA 40-year-old male patient presented with recurrent hypoglycemia and hypertension crisis. Imaging revealed a huge left retroperitoneal tumor and multiple diffuse metastases in lungs. Catecholamine was also elevated, aligning with a diagnosis of metastatic PGL. Pathology also confirmed this diagnosis. Additionally, the immunohistochemistry indicated negative expression of SDHB and gene test showed somatic SDHB mutation. Given the SDHB mutation, cyclophosphamide-vincristine-dacarbazine (CVD) chemotherapy was initiated in critical conditions. Subsequently, a significant tumor shrinkage and complete biochemical response were observed after two treatment cycles. In September 2024, CT scan revealed new pulmonary lesions. The progression-free survival (PFS) with CVD chemotherapy was 24 months.ConclusionThis report reviews the distinct clinical and biochemical characteristics and treatment approaches of SDHB-mutated paragangliomas, emphasizing that the significance of incorporating both genetic testing and immunohistochemical analysis in clinical practice.